R=(4-0.25x)(6+x)

Simple and best practice solution for R=(4-0.25x)(6+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for R=(4-0.25x)(6+x) equation:



=(4-0.25R)(6+R)
We move all terms to the left:
-((4-0.25R)(6+R))=0
We add all the numbers together, and all the variables
-((-0.25R+4)(R+6))=0
We multiply parentheses ..
-((+0R^2+0R+4R+24))=0
We calculate terms in parentheses: -((+0R^2+0R+4R+24)), so:
(+0R^2+0R+4R+24)
We get rid of parentheses
0R^2+0R+4R+24
We add all the numbers together, and all the variables
R^2+5R+24
Back to the equation:
-(R^2+5R+24)
We get rid of parentheses
-R^2-5R-24=0
We add all the numbers together, and all the variables
-1R^2-5R-24=0
a = -1; b = -5; c = -24;
Δ = b2-4ac
Δ = -52-4·(-1)·(-24)
Δ = -71
Delta is less than zero, so there is no solution for the equation

See similar equations:

| p+7.6=32.1 | | 9x+8+4x+13+2x-6=180 | | 3-2=3x-12 | | 6(x-3)=180/15 | | 4m+2m=-24 | | 2x-5=1-4x/3 | | -10+7x=5×+8 | | -19=-6k-7k | | (3x+4)(x-2)=7 | | p+8=15.1 | | x/1.2=-8 | | (3x-9)=(25+15) | | 6=(r+52/–7) | | 3x-5=1-4x/3 | | 4+2m=-10 | | x-59=149 | | 7^(8+x)=11 | | 3-13x=25 | | 6=r+52/–7 | | 1.75=n/15.2 | | -14+2m=-10 | | 4.2x=4.2+6 | | 3(9v-8)=31 | | 9+2m=33 | | 2x-6=6;0 | | 3(9v-9)=31 | | 3y-18=132 | | 10x+7=3x+10 | | 5x+3/4=1 | | -7x/2+6/9=-1x+1/3 | | 25=1.23+10x24 | | 2y-5.2=1.8-3 |

Equations solver categories